Necesidad de reformar el art. 1029 del código civil en cuanto a regular la cuota hereditaria en casos de herederos con discapacidad - Román Yánez, Daysi María del Cisne (2014)
The chosen topic for this thesis enunciates: "NECESSITY TO REFORM ART. 1029 OF THE CIVIL CODE As for REGULATING THE HEREDITARY QUOTA IN CASES OF HEIRS WITH DISCAPACIDAD"; in the same one they thought about as objective to "Carry out a juridical, critical and doctrinal study of the Civil Code, Art. 1029, on the hereditary quota settled down in the partition of goods, considering the case of the discapacitados." In a same way the hypothesis enunciates "The lack of a hereditary bigger quota, it doesn't allow that the heir with discapacidad can take a good quality of life, due to the special requirements that his condition demands" him/her. To be able to end up checking each one of these expressions, I carried out a bibliographical investigation that served as foundation for our same field investigation that was sustained with the opinion of the professionals of the branch of the Right that you/they offered a valuable contribution and that it allowed to establish the necessity to increase the hereditary quota for people with discapacidad according to the grade of difficulty that they show up. It is established therefore that the investigation framed in a doctrinal deep juridical analysis, enjoys of the validity and dependability that the professional approaches of lawyers with vast experience, for finally to present the conclusions, recommendations and the artificial reformation to the Code of the Childhood and Adolescence that I propose as solution alternative to this problem.